2013
DOI: 10.1161/atvbaha.112.00006
|View full text |Cite|
|
Sign up to set email alerts
|

Rhodocetin-αβ–induced Neuropilin-1–cMet Association Triggers Restructuring of Matrix Contacts in Endothelial Cells

Abstract: Objective-The snake venom component rhodocetin-αβ (RCαβ) stimulates endothelial cell motility in an α2β1 integrinindependent manner. We aimed to elucidate its cellular and molecular mechanisms. Methods and Results-We identified neuropilin-1 (Nrp1) as a novel target of RCαβ by protein-chemical methods. RCαβ and vascular endothelial growth factor (VEGF)-A avidly bind to Nrp1. Instead of acting as VEGF receptor 2 coreceptor, Nrp1 associates upon RCαβ treatment with cMet. Furthermore, cell-based ELISAs and kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 36 publications
(54 reference statements)
0
22
0
Order By: Relevance
“…How MET receptor activation mediates these discrete cellular outcomes is only beginning to be addressed, with most focus on the diversity of downstream signaling pathways initiated following the activation of MET (Finsterwald and Martin, 2011; Eagleson et al, 2016). Evidence from cell lines, however, indicates that the repertoire of MET protein-interacting partners expressed by a cell also can modulate MET signaling to influence biological outcomes (Smyth and Brady, 2005; Wang et al, 2005; Zeng et al, 2006; Reshetnikova et al, 2007; DeAngelis et al, 2010; Bozkaya et al, 2012; Burghy et al, 2012; Lu et al, 2012; Niland et al, 2013). A recent coimmunoprecipitation (Co-IP)/mass spectrometry (MS) study identified the MET interactome with 72 proteins, including β-catenin, in isolated murine neocortical synaptosomes during the peak of synaptogenesis (Xie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…How MET receptor activation mediates these discrete cellular outcomes is only beginning to be addressed, with most focus on the diversity of downstream signaling pathways initiated following the activation of MET (Finsterwald and Martin, 2011; Eagleson et al, 2016). Evidence from cell lines, however, indicates that the repertoire of MET protein-interacting partners expressed by a cell also can modulate MET signaling to influence biological outcomes (Smyth and Brady, 2005; Wang et al, 2005; Zeng et al, 2006; Reshetnikova et al, 2007; DeAngelis et al, 2010; Bozkaya et al, 2012; Burghy et al, 2012; Lu et al, 2012; Niland et al, 2013). A recent coimmunoprecipitation (Co-IP)/mass spectrometry (MS) study identified the MET interactome with 72 proteins, including β-catenin, in isolated murine neocortical synaptosomes during the peak of synaptogenesis (Xie et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This stiffening explains the SIRS-like symptoms caused by some snake venoms (44) at the inter-and intracellular level, and it provides insight into the underlying signaling through the NRP1-MET axis and the resulting increased mechanotransduction within a confluent monolayer of tightly interlinked ECs. Within an endothelial monolayer, the molecular mode of action of RCab is based on its binding to NRP1 and, thus, the formation of a ternary complex with MET as signaling receptor tyrosine kinase (29). Because of increased phosphorylation of paxillin, this causes disassembly of focal adhesions, which are the major forcetransmitting adhesion contacts of ECs with their ECM (29).…”
Section: Discussionmentioning
confidence: 99%
“…In a previous work, we identified rhodocetin-ab (RCab) as the first nonenzymatic component of a snake venom that recognizes neuropilin-1 (NRP1) on ECs (29). NRP1 is a transmembrane glycoprotein expressed inter alia in ECs, neurons, and immune cells (30).…”
mentioning
confidence: 99%
See 2 more Smart Citations